The NINDS Parkinson's disease biomarkers program. Issue 6 (7th October 2015) - Rosenthal, Liana S.; Drake, Daniel; Alcalay, Roy N.; Babcock, Debra; Bowman, F. DuBois; Chen‐Plotkin, Alice; Dawson, Ted M.; Dewey, Richard B.; German, Dwight C.; Huang, Xuemei; Landin, Barry; McAuliffe, Matthew; et al.
Abstract: Background: Neuroprotection for Parkinson's disease (PD) remains elusive. Biomarkers hold the promise of removing roadblocks to therapy development. The National Institute of Neurological Disorders and Stroke has therefore established the Parkinson's Disease Biomarkers Program to promote discovery of PD biomarkers for use in phase II and III clinical trials. Methods: Using a novel consortium design, the Parkinson's Disease Biomarker Program is focused on the development of clinical and laboratory‐based biomarkers for PD diagnosis, progression, and prognosis. Standardized operating procedures and pooled reference samples were created to allow cross‐project comparisons and assessment of batch effects. A web‐based Data Management Resource facilitates rapid sharing of data and biosamples across the research community for additional biomarker projects. Results: Eleven consortium projects are ongoing, seven of which recruit participants and obtain biosamples. As of October 2014, 1, 082 participants have enrolled (620 PD, 101 with other causes of parkinsonism, 23 essential tremor, and 338 controls), 1, 040 of whom have at least one biosample. Six thousand eight hundred ninety‐eight total biosamples are available from baseline, 6‐, 12‐, and 18‐month visits: 1, 006 DNA, 1, 661 RNA, 1, 419 whole blood, 1, 382 plasma, 1, 200 serum, and 230 cerebrospinal fluid (CSF). Quality control analysis of plasma, serum, and CSF samples indicates that almost all samples are high quality (24 of 2, 812 samples exceed acceptable hemoglobin levels). Conclusions: By making samples and data widely available, using stringent operating procedures based on existing standards, hypothesis testing for biomarker discovery, and providing a resource that complements existing programs, the Parkinson's Disease Biomarker Program will accelerate the pace of PD biomarker research. © 2015 International Parkinson and Movement Disorder Society